Chemical Analysis Program for the Time of Flight Mass Spectrometry System - Abdullah Kepceoğlu; Hamdi Şükür Kılıç (International Journal of Applied Methods in Electronics and Computers, 2016)
: In this work, we present a computer program that reads, manipulates, analyses and stores the mass spectra obtained by using Laser Time of Flight Mass Spectrometry (L-TOF-MS) system described elsewhere. This program allows users to record the characteristic parameters of experimental data such as vacuum pressure, voltages, laser power, sample name etc. both manually and automatically. Also, the obtained mass spectra can be used to investigate chemical substances (NO x , SO x , organic molecules etc.) or can be used to real time identification of the sample differences for given material database (metal oxides, alloys, paintings, healthy and cancerous tissues etc.) by using different mathematical and statistical procedures (PCA, LDA, kNN etc.). We have recently presented a simple chemical analysis procedure by starting from reading raw MS data from oscilloscope using TCP/IP protocol and following data processing steps. We have a great success to reduce the numbers of steps and time duration consumed for the following procedure.